Dry : (Harvard University Press, 2006)
Water is in the air we breathe and beneath the ground we walk on. The very substance of life, it makes up as much as 60 percent of the human body. And yet, for one billion people there is such a thing as life without water. These are the people we meet in Dry--those who live in the dry lands of Africa, Asia, the Pacific, and the Americas, eking out an existence at once remarkable and mundane between craggy mountains, near oases, or close to well-springs surrounded by cracked earth or shifting sands.